The Influence Of Brand Image, Product Quality, And Price On Consumer Purchase Decisions On The Shopee E-Commerce Platform - Popon Srisusilawati; Dian Meliza; Ahmad (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2026)
This study aims to analyze the influence of brand image, product quality, and price on consumer purchase decisions on the Shopee e-commerce platform. The research background is based on the rapid growth of the e-commerce industry in Indonesia, particularly the increasingly intense inter-platform competition, making it necessary to empirically examine the factors that shape consumer purchase decisions. The study employed a quantitative approach using a survey method through a Likert scale 1–5 questionnaire. The research sample consisted of 70 respondents who are active Shopee consumers. Instrument testing included validity and reliability tests, while classical assumption tests covered normality, multicollinearity, and heteroscedasticity. Data analysis was performed using multiple linear regression. The results show that brand image (X1) has a positive and significant effect on purchase decisions with a significance value of 0.000, while product quality (X2) also has a positive and significant effect with a significance value of 0.008. In contrast, price (X3) does not have a significant effect on purchase decisions with a significance value of 0.131. Simultaneously, all three variables have a significant effect on purchase decisions with F = 18.639 and significance of 0.000. The coefficient of determination (R²) of 0.459 indicates that 45.9% of the variation in purchase decisions can be explained by the three independent variables. The study concludes that brand image and product quality are the dominant factors influencing consumer purchase decisions on Shopee.